Global warming: predicting OPEC carbon dioxide emissions from petroleum consumption using neural network and hybrid cuckoo search algorithm - Haruna, Chiroma; Abdul-Kareem, Sameem; Mohd Nawi, Nazri; Gital, Abdulsam Ya'u; Shuib, Liyana; Abubakar, Adamu; Rahman, Muhammad Zubair; Herawan, Tutut (The Public Library of Science (PLoS), 2015)
Background